Beetles (Scarabaeidae, Trogidae and Silphidae) associated to a piglet carcass Sus scrofa (Linnaeus, 1758) from Los Colomos forest, Guadalajara, Jalisco - González-Hernández, A. L.; Navarrete-Heredia, J. L.; Quiroz-Rocha, G. A.; López-Caro, J. B. (Instituto de Ecología, A.C., 2013)
-